Study on Delamination Between Polymer Materials and Metals in IC Packaging Process - Cheng-Tang Pan (Polymers, 2019)
The electronic package interconnects electronic signals from one area to another and package delamination is a serious problem in the configuration of materials. This study focused on decreasing the delamination of the low-profile fine pitch ball grid array (LFBGA) and plastic ball grid array (PBGA) packages in terms of polymer thermal issue, metal bonding and bonding mechanisms. PBGA and LFBGA are a very common type of packaging processes in the electronics industry. The present study dealt first with delamination of the LFBGA packaging, through characterization and determination of physical and chemical properties such as surface roughness, surface energy, and contact angle. The relationship between surface roughness and delamination was verified through various roughness bonding experiments. In addition, the surface energy was determined by measuring the contact angle after cleaning the metal surface of Cu, Ni and Cr with Ar + O2 gas, and, this gas plasma treatment was applied to enhance the adhesive properties. The compositions of the surface were analyzed through an X-ray photoelectron spectroscopy (XPS). Also, the delamination issue between the corner of the heat sink cap and the epoxy resin was observed for delamination of the LFBGA packaging. Further, this study analyzed the PBGA packaging process through the finite element analysis simulation software ANSYS. To improve the heat sink cap delamination issue of the PBGA, a new chamfer design of the corner seat was streamlined to decrease the stress value and delamination. Besides, the simulation results demonstrated that the stress value reduced after increasing the shoulder length. The results implicate that the stress value is inversely proportional to the shoulder width and the chamfer radius. This study demonstrated that the optimization in design was able reduce the delamination phenomena in configuration material.